On Ki Hadjar Dewantara’s Philosophy of Education - Ferary, Dorothy (Nordic Journal of Comparative and International Education (NJCIE), 2021)
This comparative education article explores the purpose of education in the Indonesian context. My aim is to see if there are any differences between the purpose of education during the colonial era and present-day Indonesia. In order to do that, I draw mostly on the philosophy of Ki Hadjar Dewantara, who is regarded as the father of Indonesian education. This article is particularly relevant because the Indonesian government has recently started to critically re-examine two of the educational concepts proposed by Dewantara, which are "pendidikan karakter" (character education) and "merdeka belajar" (independent learning). In conceptualising education, Dewantara, who was influenced by Tagore, Montessori, and Fröbel, saw the importance of imparting local wisdom and values ignored by the colonial schools. Therefore, in this article, I will compare his educational views with the Dutch view of schooling during the colonial era. I will then look at Indonesia's current approach to education to find the similarities and differences of purpose relative to Dewantara's views of education. In this article, I argue that Dewantara's philosophy is still very much relevant today. I conclude that the Indonesian government should refer back to its history when defining education for its next generation.